Optimalisasi Pendidikan Pancasila di Politeknik Negeri Lampung: Upaya Penguatan Nilai-nilai Pancasila dalam Pembentukan Karakter Mahasiswa - Gilang Zulfikar; Upy Raudotul Jannahb; Maisuri Hardani; Reza Wahyuni (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the optimization of Pancasila value implementation in the Pancasila Education course and its contribution to character building among students at Politeknik Negeri Lampung. A qualitative descriptive method was employed through observation, interviews, and documentation studies. The findings reveal that Pancasila values are integrated into the curriculum, learning process, and campus culture. Lecturers apply contextual, reflective, and participatory approaches that foster students’ moral awareness, responsibility, and tolerance. Institutional support through policies and character programs strengthens the internalization of Pancasila values. Pancasila Education plays a strategic role in shaping students with integrity, nationalism, and social awareness.